And justice for all? How anti-doping responds to 'Innocent Mistakes'. Issue 2 (3rd April 2019) - Moston, Stephen; Engelberg, Terry
ABSTRACT: The WADA Strategic Plan 2015–19 includes as part of its Mission Statement, the aim to develop policies and procedures that reflect justice, equity and integrity. However, current policies and procedures for the sanctioning of athletes subvert legal maxims, such as the presumption of innocence, and punishment for all offenders, even in cases of accidental or inadvertent doping where there was neither intention, nor any performance enhancement. In this archival study, from an initial, broadly representative sample of 100 sanctions, 23 cases were identified in which sanctioned athletes either denied committing an anti-doping rule violation or denied intention to dope. Content analysis of the statements made by athletes showed that denial strategies fell into discrete categories, such as accidental doping through nutritional supplements, banned substances being present in medical treatments, accidental whereabouts violations, and accidental purchases. While some denials were credible, many were incredible, potentially reinforcing the general skepticism anti-doping authorities have towards protestations of innocence by athletes. Findings highlight the need to improve the education of athletes to prevent accidental violations. It is suggested that the introduction of a 'reasonable person' standard might help to prevent the imposition of sanctions in cases where even anti-doping tribunals acknowledge that sanctions are harsh or unfair.